Structural Inequality, Homelessness, and Moral Worth: Salvaging the Self through Sport? - Koch, Jordan; Scherer, Jay; Kafara, Rylan (Journal of contemporary ethnography, 2020)
This urban ethnography explores how a group of men experiencing homelessness collectively produced an economy of moral worth and socially beneficial labor within and through a weekly sport-for-development program in the distinct settler-colonial context of Edmonton, Alberta. For over two decades, weekly floor hockey games have been organized by local health workers as part of a broader sport-based intervention/corrective aimed, in part, at reforming Edmonton’s urban ‘underclass’, one that is decidedly Indigenous. Drawing upon three-years of ethnographic field notes and interviews with ten men aged 25–42 years, our analysis revealed how these weekly sporting interludes served as convivial, safe, and consistent events that nurtured the development of long-term meaningful relationships with other participants and social workers, as well as a genuine sense of community. The weekly floor hockey matches were, thus, powerful sites in the broader struggle for what David Snow and Leon Anderson (1993) have called “salvaging the self” for men who embodied a repertoire of trauma and who are regularly positioned as morally devalued subjects who lacked personal responsibility and self-governance.